2018
DOI: 10.1371/journal.pone.0191462
|View full text |Cite
|
Sign up to set email alerts
|

Euglena gracilis Z and its carbohydrate storage substance relieve arthritis symptoms by modulating Th17 immunity

Abstract: Euglena gracilis Z is a microorganism classified as a microalga and is used as a food or nutritional supplement. Paramylon, the carbohydrate storage substance of E. gracilis Z, is reported to affect the immunological system. This study evaluated the symptom-relieving effects of E. gracilis Z and paramylon in rheumatoid arthritis in a collagen-induced arthritis mouse model. The efficacy of both substances was assessed based on clinical arthritis signs, as well as cytokine (interleukin [IL]-17, IL-6, and interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…In a previous study, oral administration of paramylon significantly reduces the secretion of the cytokines IL-17, IL-6, and IFN-γ in lymphoid tissues, resulting in suppression of the onset of arthritis in rodent models (37). Paramylon improved the symptoms of atopic dermatitis and decreased the secretion of IL-4, IFN-γ, IL-18, and IL-12 in NC/Nga mice (23).…”
Section: Discussionmentioning
confidence: 81%
“…In a previous study, oral administration of paramylon significantly reduces the secretion of the cytokines IL-17, IL-6, and IFN-γ in lymphoid tissues, resulting in suppression of the onset of arthritis in rodent models (37). Paramylon improved the symptoms of atopic dermatitis and decreased the secretion of IL-4, IFN-γ, IL-18, and IL-12 in NC/Nga mice (23).…”
Section: Discussionmentioning
confidence: 81%
“…In addition, the subcutaneous application of β-1,3-glucan extracted from Saccharomyces cerevisiae in 20 children with asthma increased serum levels of the anti-inflammatory cytokine IL-10 and simultaneously reduced symptom scores [10]. The oral intake of paramylon has been found to reduce cytokine secretion and relieve arthritis symptoms in mice by modulating Th17 immunity [44], while studies have suggested that Euglena and paramylon could reduce upper respiratory tract infection symptoms and protect against influenza virus infection [13,45]. Here, we found that IP Euglena and paramylon injection stimulated DCs in PPs in vivo, with stronger Ca 2+ signaling observed with paramylon treatment; thus, paramylon may be the active component of Euglena that affects the immunological system.…”
Section: Discussionmentioning
confidence: 99%
“…The storage polysaccharide paramylon in Euglena regulates the immune balance. Previous studies of mouse models have confirmed that the ingestion of Euglena or paramylon alleviates the symptoms of influenza infection [ 11 ], rheumatoid arthritis [ 43 ], and atopic dermatitis [ 44 ]. The autonomic nervous system is involved in the regulation of immunity, and immunity is generally enhanced in situations where the parasympathetic nervous system is dominant, contributing to defense against infection [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%